2018
DOI: 10.2147/cmar.s160186
|View full text |Cite
|
Sign up to set email alerts
|

INHBA upregulation correlates with poorer prognosis in patients with esophageal squamous cell carcinoma

Abstract: PurposeINHBA, which encodes a member of the TGF-beta superfamily of proteins, has been identified to play a critical role in different types of cancer. However, its clinical significance in esophageal squamous cell carcinoma (ESCC) has never been reported.Patients and methodsIn this study, we collected 239 ESCC paraffin-embedded specimens and measured the expression of INHBA with immunohistochemistry (IHC). The clinical and prognostic significance of INHBA expression was statistically analyzed. What is more, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…By further analyzing our previously published gene expression microarray data from these cell lines (14, 29), we found that both IL13R α 2 and INHBA exhibit increased expression levels in metastatic compared to non-metastatic breast cancer cells and that overexpression of both genes can similarly predict worse DMFS of patients with grade 3 tumors. This is consistent with previous reports suggesting that INHBA overexpression or increased Activin A plasma levels are associated with poor prognosis in lung, gastric, pancreatic and esophageal cancers (3740). Our data presented here also demonstrate that shRNA-mediated depletion of INHBA in metastatic breast cancer cells led to suppression of IL13Rα2 mRNA and protein levels, whereas treatment of non-metastatic cells with Activin A resulted in upregulation of IL13Rα2 expression.…”
Section: Discussionsupporting
confidence: 93%
“…By further analyzing our previously published gene expression microarray data from these cell lines (14, 29), we found that both IL13R α 2 and INHBA exhibit increased expression levels in metastatic compared to non-metastatic breast cancer cells and that overexpression of both genes can similarly predict worse DMFS of patients with grade 3 tumors. This is consistent with previous reports suggesting that INHBA overexpression or increased Activin A plasma levels are associated with poor prognosis in lung, gastric, pancreatic and esophageal cancers (3740). Our data presented here also demonstrate that shRNA-mediated depletion of INHBA in metastatic breast cancer cells led to suppression of IL13Rα2 mRNA and protein levels, whereas treatment of non-metastatic cells with Activin A resulted in upregulation of IL13Rα2 expression.…”
Section: Discussionsupporting
confidence: 93%
“…There are also reports in the literature that the effect of suppressing the development of colon cancer can be achieved by immunosuppression of CXCL3 [23][24][25][26][27]. INHBA has a significant relationship with the occurrence and development of gastric, esophageal, and ovarian cancers, and studies have reported that the immunosuppressive treatment of INHBA can reduce the rate of deterioration of gastric and ovarian cancers [28][29][30]. STC1 can promote the metastasis of colon cancer [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports in the literature that the effect of suppressing the development of colon cancer can be achieved by immunosuppression of CXCL3 [12][13][14][15][16]. INHBA has a significant relationship with the occurrence and development of gastric, esophageal, and ovarian cancers, and studies have reported that the immunosuppressive treatment of INHBA can reduce the rate of deterioration of gastric and ovarian cancers [17][18][19]. STC1OXTR, and UCN can promote the metastasis of colon cancer [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%